2003
DOI: 10.1126/science.1078470
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hydroxyl Ions in Bone Mineral by Solid-State NMR Spectroscopy

Abstract: Previous measurements of the hydroxyl (OH-) ion content of the calcium phosphate crystals of bone mineral have indicated a substantial depletion or near-absence of OH-, despite its presumed status as a constituent of the hydroxyapatite lattice. Analytical methods for determining bone crystal OH- content have depended on procedures or assumptions that may have biased the results, such as chemical pretreatment to eliminate interference from the organic matrix. We demonstrate a two-dimensional solid-state nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
263
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(287 citation statements)
references
References 20 publications
20
263
0
4
Order By: Relevance
“…For example, Xu et al [8] have suggested that in hydroxyapatite the hydroxide ions move under pressures above 3 GPa. There is less hydroxide in bone than in hydroxyapatite [25]. Nonetheless, movement of any hydroxide would influence the larger phosphate, some of which is adjacent to the column of remaining hydroxide, more than the smaller carbonate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xu et al [8] have suggested that in hydroxyapatite the hydroxide ions move under pressures above 3 GPa. There is less hydroxide in bone than in hydroxyapatite [25]. Nonetheless, movement of any hydroxide would influence the larger phosphate, some of which is adjacent to the column of remaining hydroxide, more than the smaller carbonate.…”
Section: Discussionmentioning
confidence: 99%
“…Citrate in bone is fundamentally different from carbonate, fluoride, sodium, magnesium, hydroxide (29), calcium, or phosphate ions, in that it is too large to be incorporated into the apatite crystal lattice. Therefore, bound citrate must remain an interfacial component that affects properties of the bone nanocomposite more profoundly than do simple substitutions of carbonate for phosphate or of sodium for calcium.…”
Section: Resultsmentioning
confidence: 99%
“…The environment and structure of the citrate anion in OCPcitrate are both readily probed by 13 C Bloch decay (BD) and cross-polarization (CP) NMR spectra of the material (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the possibility of dynamic disorder by cooling a sample of OCP-citrate to 200 K and rerecording 13 C CP magic angle spinning NMR spectra. Cooling the sample to 200 K does not change the relative intensities of the CH 2 (1) and CH 2 (2) signals (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation